Prinsip Hifz Al-Mal dalam Tanggung Jawab atas Keterlambatan Penerbangan: The Principle of Hifz Al-Mal in Responsibility for Flight Delays - Anugrah, Dikha; Yoga Nugraha, Enggun (Faculty of Law Hang Tuah University, 2025)
This paper aims to analyze airline liability for flight delays from the perspective of Islamic law, particularly through the principle of hifz al-mal as a form of protection for passengers’ economic rights. The study employs a descriptive method with a qualitative approach using library research. Within the framework of an ijarah contract, airlines are obligated to fulfill services as agreed, including punctuality. Delays that result in financial losses necessitate compensation, both under positive law and Islamic principles. The hifz al-mal principle emphasizes the importance of safeguarding financial rights against unjust harm. Therefore, compensation such as ticket refunds, accommodation, or other remedies must be provided proportionally and fairly. This study shows that applying Islamic legal principles can strengthen justice in contractual relations between airlines and passengers.